Teacher’s Questioning Strategy in Classroom Interaction - Sintia Ekawati; Kisman Salija; Maemuna Muhayyang (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This research aimed to find out the questioning strategy used by teacher, the ways of the teacher use the questioning strategy and the ways of the teacher's questioning strategy help students to be more active in learning English at SMP Telkom Makassar. This research applied descriptive qualitative method. The data were collected from the observation by video recorder and interview by audio recorder. The data was taken from an English teacher at SMP Telkom Makassar. The result of this research showed that the teacher employed prompting questions and probing question. The teacher applied prompting question and probing question by giving clues or instructions to questions, guiding students to easily answer questions and explore specific questions so that it can help students to be more active and communicative in the learning process. It can be concluded that the questioning strategy used by the teacher, namely prompting questions and probing questions, can help students to be more active and communicative in the learning process.